2020
DOI: 10.1007/s11356-020-09540-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrated monoaromatic hydrocarbons (nitrophenols, nitrocatechols, nitrosalicylic acids) in ambient air: levels, mass size distributions and inhalation bioaccessibility

Abstract: Nitrated monoaromatic hydrocarbons (NMAHs) are ubiquitous in the environment and an important part of atmospheric humic-like substances (HULIS) and brown carbon. They are ecotoxic and with underresearched toxic potential for humans. NMAHs were determined in size-segregated ambient particulate matter collected at two urban sites in central Europe, Ostrava and Kladno, Czech Republic. The average sums of 12 NMAHs (Σ12NMAH) measured in winter PM10 samples from Ostrava and Kladno were 102 and 93 ng m−3, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Nitrocatechols have been found as tracer compounds in particulate matter emitted during biomass burning, correlating well with the levoglucosan and NO x levels (Kitanovski et al, 2012b, a;Salvador et al, 2021). In organic aerosols, the 4-nitrocatechol concentration exceeds in some cases 150 ng m −3 , whereas for methylated nitrocatechols the overall concentration can be as high as 821 ng m −3 (Iinuma et al, 2010;Kitanovski et al, 2021). These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood-burning use.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nitrocatechols have been found as tracer compounds in particulate matter emitted during biomass burning, correlating well with the levoglucosan and NO x levels (Kitanovski et al, 2012b, a;Salvador et al, 2021). In organic aerosols, the 4-nitrocatechol concentration exceeds in some cases 150 ng m −3 , whereas for methylated nitrocatechols the overall concentration can be as high as 821 ng m −3 (Iinuma et al, 2010;Kitanovski et al, 2021). These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood-burning use.…”
Section: Introductionmentioning
confidence: 72%
“…These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood-burning use. However, in these studies, all identified nitrocatechols may cover up to 96 % of the nitrated monoaromatic hydrocarbons found in PM 10 samples (Kitanovski et al, 2021). 4-nitrocatechol was found in the reaction of guaiacol initiated by OH radicals in the presence of NO x (Lauraguais et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Nitrocatechols have been found as tracer compounds in particulate matter emitted during biomass burning, correlating well with the levoglucosan and NOx levels (Kitanovski et al, 2012b(Kitanovski et al, , 2012aSalvador et al, 2021). In organic aerosols the 4-nitrocatechol concentration exceeds in some cases 150 ng × m -3 while for methylated nitrocatechols the overall concentration is as high as 821 ng × m -3 (Iinuma et al, 2010;Kitanovski et al, 2020). These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood burning use.…”
Section: Introductionmentioning
confidence: 73%
“…These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood burning use. However, in these studies, all identified nitrocatechols seem to cover up to 96% of the nitrated monoaromatic hydrocarbons found in PM10 samples (Kitanovski et al, 2020). 4-nitrocatechol was https://doi.org/10.5194/acp-2021-553 Preprint.…”
Section: Introductionmentioning
confidence: 83%
“…These high concentrations of nitrated monoaromatic hydrocarbons were determined in the winter season and have been correlated with household wood burning use. However, in these studies, all identified nitrocatechols seem to cover up to 96% of the nitrated monoaromatic hydrocarbons found in PM10 samples (Kitanovski et al, 2020). 4-nitrocatechol was found in the reaction of guaiacol initiated by the OH radicals in the presence of NOx (Lauraguais et al, 2014).…”
Section: Introductionmentioning
confidence: 76%